Pathogenic implications, incidence, and outcomes of COVID-19 in autoimmune inflammatory joint diseases and autoinflammatory disorders - Piero Ruscitti (Advances in Rheumatology, 2021)
Abstract As the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to spread rapidly, there are still many unresolved questions of how this virus would impact on autoimmune inflammatory joint diseases and autoinflammatory disorders. The main aim of this paper is to describe the main studies focusing their attention on COVID-19 incidence and outcomes of rheumatoid arthritis (RA), spondylarthritis (SpA), and autoinflammatory disease cohorts. We also revised possible pathogenic mechanisms associated with. Available data suggest that, in patients with RA and SpA, the immunosuppressive therapy, older age, male sex, and the presence of comorbidities (hypertension, lung disease, diabetes, CVD, and chronic renal insufficiency/end-stage renal disease) could be associated with an increased risk of infections and high rate of hospitalization. Other studies have shown that lower odds of hospitalization were associated with bDMARD or tsDMARDs monotherapy, driven largely by anti-TNF therapies. For autoinflammatory diseases, considering the possibility that COVID-19 could be associated with a cytokine storm syndrome, the question of the susceptibility and severity of SARS-CoV-2 infection in patients displaying innate immunity disorders has been raised. In this context, data are very scarce and studies available did not clarify if having an autoinflammatory disorder could be or not a risk factor to develop a more severe COVID-19. Taking together these observations, further studies are likely to be needed to fully characterize these specific patient groups and associated SARS-CoV-2 infection.